Perlindungan Hukum bagi Konsumen Depot Air Minum yang Terpapar Bacteri Escherichia Coli - Hidayat, Taupik; Ginting, Elvira Dewi (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
This study aims to analyze the legal protection given to consumers of drinking water depots who experience losses due to exposure to Escherichia coli bacteria. The research method used is a normative juridical method by analyzing the Consumer Protection Law No. 8 of 1999 regarding legal protection for consumers of drinking water depots. However, to support normative juridical research, empirical research is also needed to determine how the management of drinking water depots is carried out. The results of the study show that legal protection for drinking water depot consumers who are exposed to Escherichia coli bacteria is contained in various laws and regulations, such as the Consumer Protection Act and the Minister of Health Regulation concerning Water Quality Requirements for Sanitation Hygiene and Recreation Purposes. However, there are several obstacles in providing legal protection for consumers of drinking water depots, such as the lack of law enforcement against violations related to drinking water quality and the lack of public awareness of the importance of consuming safe and healthy drinking water. Therefore, efforts from the government and society are needed to increase awareness of the importance of drinking water quality and law enforcement against violations related to drinking water quality.